PENERAPAN TEAM BASED LEARNING DENGAN SOFTWARE GAP PADA MATA KULIAH STRUKTUR ALJABAR - Nurain Suryadinata; Nurul Farida (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2017)
The purpose of this study is to determine the achievement of learning and improving student achievement learning of TBL assisted GAP software in the course of algebra structure. This research is a quasi-experiment research with the form of Nonequivalent (Pre-Test and Post-Test) Control Group Design. The technique of collecting data using test. The data analysis technique used statistical test against pretest, posttest and n-gain score. The results of this study concluded that (1) the learning achievement of students who received learning GPL-assisted TBL software was higher than that of students who received conventional learning, (2) improvement of learning achievement of students who received learning GPL-assisted TBL software higher than students who received learning Conventional.